Electrolyte additive and preparation method thereof, electrolyte, aqueous zinc ion battery and electric equipment
By using MXene material as an electrolyte additive in aqueous zinc ion batteries to form a protective film, the problems of zinc dendrites growth, zinc corrosion and hydrogen evolution reaction are solved, and the high capacity and long cycle life of the battery are achieved.
Patent Information
- Application Number
- CN202510006807.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The growth of zinc dendrites on the surface of zinc negative electrodes in aqueous zinc ion batteries may lead to internal short circuits, zinc corrosion and passivation to produce irreversible by-products, and the hydrogen evolution reaction will cause excessive internal pressure of the battery, which may cause electrolyte leakage and battery explosion.
MXene material is used as an electrolyte additive, and mixing it with the electrolyte to form a stable protective film on the surface of the zinc negative electrode, inhibit the growth of zinc dendrites, improve the stability of the zinc negative electrode, and improve the interfacial charge transport performance of the battery during the electrochemical reaction.
Effectively alleviate the growth problem of zinc dendrites, improve the stability of zinc negative electrodes in electrolytes, improve the interfacial charge transport performance of the battery, extend the cycle life of the battery and improve capacity.
Smart Images

Figure CN119812513A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of aqueous zinc ion batteries, and specifically relates to an electrolyte additive and a preparation method thereof, an electrolyte, an aqueous zinc ion battery and electrical equipment. Background Art
[0002] Lithium-ion batteries dominate energy storage systems due to their high energy density and long cycle life. However, their development is limited by high cost, shortage of lithium resources and safety issues. Aqueous zinc-ion batteries are attractive alternatives due to the unique properties of their aqueous electrolytes, which are non-flammable and have high ionic conductivity. In addition, zinc metal is cheaper than lithium, sodium and potassium; more importantly, zinc metal has good electrochemical properties.
[0003] However, the zinc negative electrode of aqueous zinc-ion batteries has the following problems: the growth of zinc dendrites on the surface of the zinc negative electrode may penetrate the diaphragm and cause internal short circuit; zinc corrosion and passivation lead to irreversible by-products; there is a hydrogen evolution reaction at the zinc negative electrode, and the generated gas will cause excessive internal pressure of the battery, which may cause electrolyte leakage and battery explosion. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide an electrolyte additive and a preparation method thereof, an electrolyte, an aqueous zinc ion battery and an electrical device. The electrolyte additive provided in the present application can effectively alleviate the growth problem of zinc dendrites, greatly improve the stability of the zinc negative electrode in the electrolyte, improve the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction, and at the same time help the aqueous zinc ion battery maintain high capacity and long cycle life.
[0005] In a first aspect, the present application provides an electrolyte additive. According to an embodiment of the present application, the electrolyte additive includes a MXene material.
[0006] The electrolyte additive according to the embodiment of the present application can effectively alleviate the growth problem of zinc dendrites, greatly improve the stability of the zinc negative electrode in the electrolyte, improve the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction process, and at the same time help the aqueous zinc ion battery maintain high capacity and long cycle life.
[0007] In addition, the electrolyte additive according to the above embodiment of the present application may also have the following additional technical features:
[0008] In some embodiments of the present application, hydrophilic functional groups are distributed on the surface of the MXene material.
[0009] In some embodiments of the present application, the hydrophilic functional group includes at least one of an oxygen group, a hydroxyl group, a fluoro group, and a chloro group.
[0010] In some embodiments of the present application, the chemical formula of the MXene material is: m X, wherein M is selected from at least one of V, Ti, Cr, Mo, Nb, Y, Sc, Zr, Hf, Ta, and W, and X is selected from at least one of C and N, and 1≤m≤2.
[0011] In some embodiments of the present application, M is selected from V, and X is selected from C.
[0012] In some embodiments of the present application, the MXene material is a single-layer MXene material.
[0013] The second aspect of the present application proposes a method for preparing the electrolyte additive described in the above embodiment. According to an embodiment of the present application, the method comprises:
[0014] (1) mixing a halogen element hydride, a fluoride salt and water to obtain a mixed solution, wherein the electronegativity of the halogen element in the halogen element hydride is lower than that of the fluorine element;
[0015] (2) Mixing a MXene precursor with the mixed solution and reacting them to obtain a MXene material.
[0016] According to the method of the embodiment of the present application, first, the method of preparing MXene materials by in-situ generation of hydrofluoric acid containing halogen hydrides and fluoride salts can avoid direct contact with highly corrosive and toxic hydrofluoric acid, and its safety performance is relatively high. Second, during the etching process of this method, metal ions can spontaneously insert into the interlayer of MXene materials, which expands the interlayer spacing of MXene materials and reduces the interlayer van der Waals force of MXene materials, which is conducive to the formation of a few layers or a single layer of MXene materials in the subsequent steps. Third, the method of obtaining MXene materials by hydrothermal reaction etching of halogen hydrides and fluoride salts not only greatly reduces the etching time compared to conventional methods, but also the high temperature and high pressure preparation conditions can make the reaction more thorough. Fourth, the method of in-situ generation of hydrofluoric acid in the present application has a milder etchant, so a MXene material with a larger lateral size and fewer defects can be obtained, and the electronic properties and stability of the product MXene material are better.
[0017] In addition, the method according to the above embodiment of the present application may also have the following additional technical features:
[0018] In some embodiments of the present application, the method further includes: (3) mixing the MXene material obtained in step (2) with a delamination agent to obtain a single-layer MXene material.
[0019] In some embodiments of the present application, in step (1), the mass ratio of the hydride containing halogen elements to the fluoride salt is 1:(10-15); and / or, the hydride containing halogen elements includes at least one of HCl, HBr and HI; and / or, the fluoride salt includes at least one of lithium fluoride, sodium fluoride and potassium fluoride.
[0020] In some embodiments of the present application, in step (2), the reaction temperature is 50 to 300° C., and the reaction time is 10 h to 50 h.
[0021] In some embodiments of the present application, in step (3), the layering agent includes at least one of dimethyl sulfoxide, hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
[0022] The third aspect of the present application proposes an electrolyte. According to an embodiment of the present application, the electrolyte includes the electrolyte additive of the first aspect or the electrolyte additive prepared by the method of the second aspect. Therefore, the electrolyte of the present application can effectively alleviate the growth problem of zinc dendrites, greatly improve the stability of the zinc negative electrode in the electrolyte, improve the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction, and at the same time help the aqueous zinc ion battery maintain high capacity and long cycle life.
[0023] In addition, the electrolyte according to the above embodiment of the present application may also have the following additional technical features:
[0024] In some embodiments of the present application, the concentration of the MXene material in the electrolyte is 0.05 mol / L to 0.2 mol / L.
[0025] In some embodiments of the present application, an electrolyte salt is further included, and the electrolyte salt includes at least one of zinc sulfate and zinc acetate.
[0026] In some embodiments of the present application, the concentration of the electrolyte salt in the electrolyte is 1 mol / L to 3 mol / L.
[0027] In some embodiments of the present application, the contact angle between the electrolyte and the zinc sheet is 60° to 97°.
[0028] The fourth aspect of the present application proposes an aqueous zinc ion battery. According to an embodiment of the present application, the aqueous zinc ion battery includes the electrolyte of the third aspect. Thus, the zinc dendrite problem in the aqueous zinc ion battery can be effectively alleviated, the stability of the zinc negative electrode in the electrolyte can be greatly improved, the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction process can be improved, and the aqueous zinc ion battery can be helped to maintain high capacity and long cycle life.
[0029] In the fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the aqueous zinc ion battery described in the above embodiment. Therefore, the electric device has all the advantages of the aqueous zinc ion battery, which will not be repeated here.
[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD spectrum of the precursor V2AlC in Example 1 of the present application.
[0032] Figure 2 This is the XRD spectrum of the multilayer vanadium carbide in Example 1 of the present application.
[0033] Figure 3 This is the SEM image of the precursor V2AlC in Example 1 of the present application.
[0034] Figure 4 This is a SEM image of the multilayer vanadium carbide in Example 1 of the present application.
[0035] Figure 5 This is the FTIR spectrum of the target product vanadium carbide in Example 1 of the present application.
[0036] Figure 6 These are SEM images of zinc foil after being immersed in the electrolyte of Example 3, Example 5 and Comparative Example 1 of the present application for 3 days.
[0037] Figure 7 Schematic diagram of the contact angle of the electrolyte of Example 1 and Comparative Example 1 of the present application on the zinc sheet.
[0038] Figure 8 This is the EIS spectrum of Example 1 and Comparative Example 1 of the present application after cycling.
[0039] Fig. 9 It is a time-voltage curve diagram of the Zn-Zn symmetric battery of Example 1 and Comparative Example 1 of the present application.
[0040] Fig.10 This is a SEM image of the negative electrode of the Zn-Zn symmetric battery of Example 1 and Comparative Example 1 of the present application after 300 cycles.
[0041] Fig.11 These are the cycle performance diagrams of the full batteries of Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0042] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0043] In the first aspect of the present application, an electrolyte additive is proposed. According to an embodiment of the present application, the electrolyte additive includes a MXene material. The beneficial effects that can be achieved by the electrolyte additive proposed in the present application are described in detail below:
[0044] The present application provides a new type of electrolyte additive. First, the excellent conductivity of the MXene material itself can effectively induce the uniform nucleation of metallic zinc, effectively inhibit the growth of zinc dendrites on the surface of the zinc negative electrode, and reduce the generation of by-products.
[0045] Second, as an electrolyte additive, MXene materials can form a stable protective film on the surface of the zinc negative electrode during the long-term cycle of aqueous zinc-ion batteries, which not only helps to increase the specific surface area of the zinc sheet, but also isolates the direct contact between the zinc negative electrode and the electrolyte, and can effectively avoid corrosion and passivation of the zinc negative electrode and side reactions such as hydrogen evolution at the zinc negative electrode. In addition, the addition of MXene materials can improve the ionic conductivity of the electrolyte, making the charge transfer resistance of the electrolyte after adding MXene materials much smaller than that of conventional electrolyte batteries. This is mainly due to the fact that Zn 2+ The rapid diffusion at the electrode / electrolyte interface and the protective film formed by the MXene material accelerate the charge transfer, so the addition of MXene material improves the interfacial charge transport performance of aqueous zinc-ion batteries during the electrochemical reaction.
[0046] Third, the constant current charge and discharge curve of the symmetric battery with added MXene material has a smaller voltage overpotential. It can be seen that the battery with electrolyte added with MXene material has smaller polarization, more stable cycle performance and smaller zinc nucleation energy barrier. Therefore, the addition of MXene material is beneficial for aqueous zinc-ion batteries to maintain high capacity and long cycle life.
[0047] Therefore, the electrolyte additive provided in the present application can effectively alleviate the growth problem of zinc dendrites, greatly improve the stability of the zinc negative electrode in the electrolyte, improve the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction process, and at the same time help the aqueous zinc ion battery maintain high capacity and long cycle life.
[0048] In addition, compared with other methods of inhibiting zinc dendrites on the surface of zinc negative electrode, the cost of electrolyte additives is lower; and the electrolyte additives of the present application are used in combination with conventional electrolytes, which can also effectively improve the electrochemical properties of zinc ion batteries and meet the performance requirements of zinc ion batteries in different usage scenarios.
[0049] According to some specific embodiments of the present application, the surface of the above-mentioned MXene material is distributed with hydrophilic functional groups. The surface of the MXene material is distributed with hydrophilic functional groups and its own excellent conductivity can effectively induce the uniform nucleation of metallic zinc, effectively inhibit the growth of zinc dendrites on the surface of the zinc negative electrode, and reduce the generation of by-products.
[0050] According to some further specific embodiments of the present application, the hydrophilic functional group includes at least one of an oxygen group, a hydroxyl group, and a halogen group. Thus, the above-mentioned hydrophilic functional groups can effectively induce uniform nucleation of metallic zinc, effectively inhibit the growth of zinc dendrites on the surface of the zinc negative electrode, and reduce the generation of by-products. Furthermore, the above-mentioned halogen group includes at least one of a fluorine group, a chlorine group, a bromine group, and an iodine group.
[0051] According to some specific embodiments of the present application, the chemical formula of the above MXene material is: m X, wherein M is selected from at least one of V, Ti, Cr, Mo, Nb, Y, Sc, Zr, Hf, Ta, and W, X is selected from at least one of C and N, and 1≤m≤2. The above-mentioned types of MXene materials are conducive to the formation of an accordion-like morphology during the etching process, thereby facilitating the formation of a single-layer MXene material. The single-layer MXene material has a larger specific surface area, which can not only further help increase the specific surface area of the zinc sheet, but also further isolate the zinc sheet from direct contact with the electrolyte.
[0052] As a preferred embodiment, M is selected from V, and X is selected from C. Thus, the above MXene material is conducive to the formation of hydrophilic functional groups on its surface during the etching process, and the above MXene material also has metallic conductivity. At the same time, vanadium carbide is a two-dimensional inorganic compound, which is composed of transition metal carbides with a thickness of several atomic layers. In addition, vanadium carbide also has the characteristics of strong hydrophilicity, good flexibility, good chemical stability, and excellent mechanical properties.
[0053] According to some other specific embodiments of the present application, the MXene material is a single-layer MXene material. The single-layer MXene material has a larger specific surface area, which can not only further help to increase the specific surface area of the zinc sheet, but also further isolate the zinc sheet from direct contact with the electrolyte.
[0054] The second aspect of the present application provides a method for preparing the above electrolyte additive. According to an embodiment of the present application, the above method includes:
[0055] S100: mixing a halogen element hydride, a fluoride salt and water to obtain a mixed solution;
[0056] In this step, a halogen hydride (wherein the electronegativity of the halogen in the halogen hydride is lower than that of the fluorine), a fluoride salt and water are mixed, and hydrofluoric acid is generated in situ to obtain a mixed solution containing hydrofluoric acid. As a specific embodiment, the halogen hydride and deionized water can be added to the lining of a polytetrafluoroethylene reactor, and then the fluoride salt is added, and the lining of the reactor is placed on a stirrer in a fume hood and stirred until it is completely dissolved.
[0057] In the related art, the main method for preparing MXene materials is to use high-concentration hydrofluoric acid as an etchant. However, since high-concentration hydrofluoric acid is highly corrosive and toxic, it is very dangerous to the human body and the environment. Therefore, in this step, the method of in-situ generation of hydrofluoric acid is used to prepare MXene materials, which has higher safety performance. At the same time, due to the metal ions (Li + 、Na + or K + ) is inserted, and the interlayer spacing of the MXene material is expanded, which is beneficial to the formation of a single-layer MXene material in the subsequent steps.
[0058] According to some specific embodiments of the present application, in step S100, the mass ratio of the halogen element hydride to the fluoride salt is 1:(10-15), thereby further ensuring the in-situ generation of hydrofluoric acid.
[0059] In the embodiments of the present application, the specific type of the halogen element hydride is not particularly limited. As some preferred embodiments, the halogen element hydride includes at least one of HCl, HBr and HI.
[0060] In the embodiments of the present application, the specific type of the above-mentioned fluoride salt is not particularly limited. As some preferred embodiments, the fluoride salt includes at least one of lithium fluoride, sodium fluoride and potassium fluoride.
[0061] S200: mixing the MXene precursor with the mixed solution, reacting to obtain a MXene material;
[0062] In this step, the MXene precursor is mixed with the mixed liquid so as to etch the MXene precursor to form a multilayer MXene material.
[0063] However, since it takes a long time (about 6 days) to etch the layered MXene precursor with in situ generated hydrofluoric acid, a hydrothermal reaction is used in this step to etch the vanadium-based MXene.
[0064] According to some specific embodiments of the present application, the reaction temperature is 50°C to 300°C, preferably 100°C to 200°C, and the reaction time is 10h to 50h, preferably 10h to 20h. Thus, the efficiency of etching the layered MXene precursor can be further improved, and complete etching can be ensured.
[0065] As a specific embodiment, the MXene precursor is slowly added to the lining of the reactor containing the mixed liquid, and stirring is continued until dissolved. Then the reactor is placed in a blast furnace, and the reaction temperature (50°C to 300°C) and reaction time (10h to 50h) are set. After the reaction is completed, the reacted solution is poured into a centrifuge tube, deionized water is added, and then shaken. Then it is placed in a centrifuge for centrifugation, and the upper layer of liquid is poured off after the centrifugation stops. Repeat the operation until the pH is neutral and collect the precipitate to obtain a multilayer MXene material.
[0066] In the embodiments of the present application, the chemical formula of the MXene precursor is MAX phase, M represents a transition metal element; A represents an aluminum element; and X represents carbon and / or nitrogen. MXene precursors include Ti3AlC2, Ti2AlC, Ta4AlC3, TiNbAlC, (V 0.5 Cr 0.5 )3AlC2, V2AlC, Nb2AlC, Nb4AlC3, Ti3AlCN or a mixture of two or more thereof.
[0067] S300: mixing the MXene material obtained in step S200 with a delamination agent to obtain a single-layer MXene material;
[0068] In this step, the MXene material obtained in step S200 is mixed with a stratification agent, the multilayer MXene material is stratified, and separated by centrifugation or oscillation to obtain a single-layer MXene material.
[0069] In the embodiments of the present application, the specific type of the above-mentioned layering agent is not particularly limited. As some preferred embodiments, the layering agent includes at least one of dimethyl sulfoxide, hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
[0070] As a specific embodiment, the precipitate obtained in step S200 (i.e., multilayer MXene material) is dissolved in deionized water, and then the stratification agent is added and placed in a fume hood and stirred evenly so as to stratify the multilayer MXene material to form a single-layer MXene material. After stirring, the solution is transferred to a centrifuge tube, and the stratification agent solution is repeatedly centrifuged to remove the stratification agent solution, and then the precipitate is collected. Deionized water is then added to the precipitate, and then centrifuged at a low speed. The purpose of this step is to separate the incompletely etched precursor from the layered MXene material, and then collect the upper black liquid, in which the MXene material is dissolved. Finally, the collected black liquid is centrifuged at high speed, and the lower black precipitate is collected to obtain a single-layer MXene material.
[0071] According to the method for preparing the above-mentioned electrolyte additive in an embodiment of the present application, first, the MXene material is prepared by a method involving halogen element hydrides and fluoride salts to in-situ generate hydrofluoric acid, which can avoid direct contact with highly corrosive and toxic hydrofluoric acid and has a higher safety performance.
[0072] Second, during the etching process, the metal ions (Li + 、Na + or K + ) can be spontaneously inserted into the interlayer of MXene materials, which expands the interlayer spacing of MXene materials and reduces the interlayer van der Waals force of MXene materials, which is beneficial to the formation of few-layer or single-layer MXene materials in subsequent steps.
[0073] Third, the method of using halogen hydride and fluoride salt to hydrothermally etch to obtain MXene materials not only greatly reduces the etching time compared to conventional methods, but the high temperature and high pressure preparation conditions can also make the reaction more thorough.
[0074] Fourth, the in-situ generation of hydrofluoric acid in the present application uses a milder etchant, so MXene materials with larger lateral dimensions and fewer defects can be obtained, and the electronic properties and stability of the product MXene materials are better.
[0075] Fifth, the use of closed reactor conditions during the reaction process can not only avoid the unnecessary consumption of reactants due to the generation of gases during the reaction, but also avoid material oxidation and improve purity.
[0076] The third aspect of the present application proposes an electrolyte. According to an embodiment of the present application, the electrolyte includes the electrolyte additive of the first aspect or the electrolyte additive prepared by the method of the second aspect. Therefore, first, MXene material is used as an electrolyte additive. The surface of the MXene material is distributed with hydrophilic functional groups and its own excellent electrical conductivity can effectively induce the uniform nucleation of metallic zinc, effectively inhibit the growth of zinc dendrites on the surface of the zinc negative electrode, and reduce the generation of by-products. Second, MXene material as an electrolyte additive can form a stable protective film on the surface of the zinc negative electrode during the long-term cycle of the aqueous zinc ion battery, which not only helps to increase the specific surface area of the zinc sheet, but also can isolate the direct contact between the zinc negative electrode and the electrolyte, and can effectively avoid the corrosion and passivation of the zinc negative electrode and the side reactions such as hydrogen evolution at the zinc negative electrode. In addition, the addition of MXene material can improve the ionic conductivity of the electrolyte, so that the electrolyte after adding MXene material is much smaller than the charge transfer resistance of conventional electrolyte batteries. This is mainly due to the rapid diffusion of Zn2+ at the electrode / electrolyte interface and the protective film formed by the MXene material, which accelerates the charge transfer. Therefore, the addition of MXene materials improves the interfacial charge transport performance of aqueous zinc ion batteries during electrochemical reactions. Third, the constant current charge-discharge curve of the symmetrical battery with the addition of MXene materials has a smaller voltage overpotential. It can be seen that the battery with the electrolyte of the MXene material has a smaller polarization, a more stable cycle performance, and a smaller zinc nucleation energy barrier. Therefore, the addition of MXene materials is conducive to the aqueous zinc ion battery to maintain high capacity and long cycle life. Thus, the electrolyte of the present application can effectively alleviate the growth problem of zinc dendrites, greatly improve the stability of the zinc negative electrode in the electrolyte, improve the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction, and at the same time help the aqueous zinc ion battery to maintain high capacity and long cycle life.
[0077] According to some specific embodiments of the present application, the concentration of MXene material in the electrolyte is 0.05mol / L~0.2mol / L, and as an example it can be 0.05mol / L, 0.1mol / L, 0.15mol / L, 0.2mol / L, etc. By limiting the concentration of MXene material in the electrolyte to the above range, the growth problem of zinc dendrites can be further effectively alleviated, the stability of the zinc negative electrode in the electrolyte can be further improved, and the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction can be further improved, and at the same time, it is further beneficial for the aqueous zinc ion battery to maintain high capacity and long cycle life.
[0078] According to some further specific embodiments of the present application, the electrolyte further includes an electrolyte salt, and the electrolyte salt includes at least one of zinc sulfate and zinc acetate, which provides the necessary Zn for the electrochemical reaction of the aqueous zinc ion battery. 2+Ions, and the electrolyte salt is matched with the electrolyte additive of the present application, which can also effectively improve the electrochemical performance of the zinc ion battery and meet the performance requirements of the zinc ion battery in different usage scenarios.
[0079] According to some specific embodiments of the present application, the concentration of the electrolyte salt in the electrolyte is 1 mol / L to 3 mol / L, and as an example, it can be 1 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 3 mol / L, etc., thereby further ensuring that the necessary Zn is provided for the electrochemical reaction of the aqueous zinc ion battery. 2+ Ions can also further ensure the improvement of the electrochemical performance of zinc-ion batteries and meet the performance requirements of zinc-ion batteries in different usage scenarios.
[0080] According to some other specific embodiments of the present application, the contact angle between the electrolyte and the zinc sheet is 60° to 97°, thereby effectively reducing the contact angle between the electrolyte and the zinc sheet, that is, after the electrolyte additive of the present application is added to the electrolyte, the wettability of the interface between the zinc electrode and the electrolyte is improved, which is beneficial to the uniform deposition of zinc ions and the formation of a smooth SEI film on the surface of the electrode sheet.
[0081] The fourth aspect of the present application proposes an aqueous zinc ion battery. According to an embodiment of the present application, the aqueous zinc ion battery includes the electrolyte of the third aspect. Thus, the zinc dendrite problem in the aqueous zinc ion battery can be effectively alleviated, the stability of the zinc negative electrode in the electrolyte can be greatly improved, the interfacial charge transport performance of the aqueous zinc ion battery during the electrochemical reaction process can be improved, and the aqueous zinc ion battery can be helped to maintain high capacity and long cycle life.
[0082] The aqueous zinc-ion battery of the present application may include aqueous zinc-ion battery monomers, aqueous zinc-ion battery modules, and aqueous zinc-ion battery packs. In some embodiments, aqueous zinc-ion battery monomers may be assembled into aqueous zinc-ion battery modules, and the number of aqueous zinc-ion battery monomers contained in the aqueous zinc-ion battery modules may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the aqueous zinc-ion battery modules. In some embodiments, aqueous zinc-ion battery modules may also be assembled into aqueous zinc-ion battery packs, and the number of aqueous zinc-ion battery modules contained in the aqueous zinc-ion battery packs may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the aqueous zinc-ion battery packs.
[0083] The fifth aspect of the present application provides an electrical device, the electrical device comprising the aqueous zinc ion battery of the fourth aspect. Thus, the electrical device has excellent service life and safety performance.
[0084] Aqueous zinc-ion battery cells, aqueous zinc-ion battery modules, and aqueous zinc-ion battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile devices (e.g., mobile phones, laptops, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0085] As an electrical device, an aqueous zinc-ion battery, an aqueous zinc-ion battery module or an aqueous zinc-ion battery pack can be selected according to its usage requirements.
[0086] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of aqueous zinc ion batteries, an aqueous zinc ion battery pack or aqueous zinc ion battery module may be used.
[0087] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and an aqueous zinc ion battery cell may be used as a power source.
[0088] It should be noted that the characteristics and advantages described above for aqueous zinc ion batteries are also applicable to the electrical equipment and will not be repeated here.
[0089] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0090] Example 1
[0091] 1) Preparation of MXene materials:
[0092] High-temperature calcination: First, weigh 3.58g of vanadium powder, 1.0405g of aluminum powder and 0.38g of graphite powder, mix them and grind them evenly in a mortar. Then use a spoon to spread the evenly ground material into a small magnetic boat, and then put the small magnetic boat into a high-temperature tube furnace. Heat to 1550°C under an argon atmosphere, then keep warm for 4 hours under an argon atmosphere, wait for natural cooling and then take out the small magnetic boat. Put the obtained gray block solid into a mortar and continue grinding to obtain the black precursor V2AlC powder.
[0093] High temperature and high pressure chemical etching: Add hydrochloric acid and deionized water to the lining of a polytetrafluoroethylene reactor, then add 0.5g of lithium fluoride, and place the lining of the reactor on a stirrer in a fume hood and stir until completely dissolved. Among them, the mass ratio of HCl to lithium fluoride in hydrochloric acid is 1:12. Then slowly add 0.5g of precursor V2AlC powder and continue stirring until dissolved. Place the reactor in a blast furnace. Set the reaction temperature and reaction time, the reaction temperature is 150°C, and the reaction time is 15h. After the reaction is completed, pour the reacted solution into a centrifuge tube, add deionized water, and shake well. Then put it in a centrifuge for centrifugation, and pour off the upper layer of liquid after the centrifugation stops. Repeat the operation until the pH is neutral, collect the precipitate, and obtain a multilayer vanadium carbide sample, which is sealed and stored by passing argon.
[0094] Layering: Dissolve the precipitate obtained in the above steps in deionized water, add tetramethylammonium hydroxide and stir evenly in a fume hood. After stirring, transfer the solution to a centrifuge tube, centrifuge repeatedly to remove the tetramethylammonium hydroxide alkaline solution, and then collect the precipitate. Add deionized water to the precipitate, shake well, and centrifuge at a low speed. The purpose of this step is to separate the unreacted precursor from the layered vanadium carbide, and then collect the upper black liquid, which contains layered vanadium carbide. Finally, the collected upper black liquid is centrifuged at high speed, and the lower black precipitate is collected. The obtained sample is a single-layer vanadium carbide with a chemical formula of V2C.
[0095] XRD tests were performed on the precursor V2AlC and multilayer vanadium carbide in Example 1, and the results are as follows: Figure 1 and Figure 2 The precursor V2AlC and multilayer vanadium carbide in Example 1 were tested by SEM, and the results are shown in Figure 3 and Figure 4 The single layer of vanadium carbide in Example 1 was tested by FTIR, and the results are as follows Figure 5 shown.
[0096] from Figure 1 and Figure 2 It can be seen that all the diffraction peaks belonging to the precursor V2AlC are Figure 2 All of them disappeared, and the (002) diffraction peak of vanadium carbide shifted to the left and there were no other impurity peaks, which indicated that vanadium-based MXene was successfully prepared and the interlayer spacing became larger.
[0097] from Figure 3 It can be found that the morphology of the precursor V2AlC is blocky and has no layered structure. Figure 4 The morphology of MXene obtained by hydrothermal reaction etching appears accordion-like, and the MXene layered structure is completely opened.
[0098] Figure 5FTIR spectrum of vanadium carbide. The main characteristic peaks correspond to 3428 cm -1 、1641cm -1 、972cm -1 and 587cm -1 , proving the existence of -OH, -C=O, -CF and -VO functional groups on its surface, among which -OH is a hydrophilic functional group.
[0099] 2) Electrolyte preparation: Add vanadium carbide solution to zinc sulfate solution to form an electrolyte, wherein the concentration of vanadium carbide in the electrolyte is 0.1 mol / L, and the concentration of zinc sulfate in the electrolyte is 1 mol / L.
[0100] 3) Preparation of positive electrode materials:
[0101] In this embodiment, the positive electrode material manganese dioxide nanorods are prepared by a hydrothermal method. The specific method is as follows: Place the inner liner of a reactor made of polytetrafluoroethylene on a stirring table and place it in a fume hood. First, add 2mL of 98wt% sulfuric acid and 75mL of deionized water, then add 1.264g of potassium permanganate to the inner liner of the reactor in small amounts several times, stir for 15 minutes, then pass argon gas into the solution for protection, and finally load the inner liner into the reactor. The reactor is then placed in a 140°C blast furnace for reaction for 3.5 hours. After the reaction is completed, cool naturally to room temperature and take out the reactor. Pour the solution into a centrifuge tube and rinse it with deionized water. Then put the sample into a vacuum oven and dry it at 80°C for one night.
[0102] 4) Preparation of manganese dioxide pole piece:
[0103] Weigh manganese dioxide nanorods, Super P and PVDF in a mass ratio of 7:2:1, then pour them into a mortar for grinding. During the grinding process, add NMP to the mortar in small amounts and multiple times to make the slurry evenly ground. Finally, use a scraper to evenly coat the slurry on a 4×4 cm 2 The titanium foil was then placed in a vacuum oven and dried overnight.
[0104] 5) Preparation of zinc sheet electrode:
[0105] Use a gun to cut the zinc foil coated with vanadium carbide into pole pieces with a diameter of 12 mm.
[0106] 6) Battery assembly: This embodiment uses zinc symmetrical cells and zinc-manganese dioxide full cells. In the symmetrical cell, the positive and negative electrodes are the same zinc sheets. The negative electrode shell, spring sheet, gasket, negative electrode sheet, electrolyte, diaphragm, positive electrode sheet, electrolyte and positive electrode shell are assembled in sequence. After assembly, the battery is pressed with a tablet press and then left to stand in the air for 8 hours for the next electrochemical test.
[0107] Example 2
[0108] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being the electrolyte:
[0109] 2) The concentration of vanadium carbide in the electrolyte is 0.05 mol / L.
[0110] Example 3
[0111] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being the electrolyte:
[0112] 2) The concentration of vanadium carbide in the electrolyte is 0.15 mol / L.
[0113] Example 4
[0114] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being the electrolyte:
[0115] 2) The concentration of vanadium carbide in the electrolyte is 0.2 mol / L.
[0116] Example 5
[0117] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being the electrolyte:
[0118] 2) The concentration of vanadium carbide in the electrolyte is 0.3 mol / L.
[0119] Example 6
[0120] The preparation method of this embodiment is basically the same as that of Embodiment 1, and the only difference is the type of MXene material: the MXene material is Ti3C2.
[0121] Example 7
[0122] The preparation method of this embodiment is basically the same as that of Embodiment 1, and the only difference is the type of MXene material: the MXene material is Nb4C3.
[0123] Example 8
[0124] The preparation method of this embodiment is basically the same as that of Embodiment 1, and the only difference is the type of MXene material: the MXene material is Ti3N2.
[0125] Example 9
[0126] The preparation method of this embodiment is basically the same as that of Embodiment 1, and the only difference is the type of MXene material: the MXene material is Mo2C.
[0127] Example 10
[0128] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0129] 1) Preparation of MXene materials:
[0130] High temperature and high pressure chemical etching: The mass ratio of HCl to lithium fluoride in hydrochloric acid is 1:10.
[0131] The chemical formula of the prepared MXene material is V2C.
[0132] Embodiment 11
[0133] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0134] 1) Preparation of MXene materials:
[0135] High temperature and high pressure chemical etching: The mass ratio of HCl to lithium fluoride in hydrochloric acid is 1:15.
[0136] The chemical formula of the prepared MXene material is V2C.
[0137] Example 12
[0138] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0139] 1) Preparation of MXene materials:
[0140] High temperature and high pressure chemical etching: reaction temperature is 70°C and reaction time is 50h.
[0141] The chemical formula of the prepared MXene material is V2C.
[0142] Example 13
[0143] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0144] 1) Preparation of MXene materials:
[0145] High temperature and high pressure chemical etching: reaction temperature is 200°C and reaction time is 10h.
[0146] The chemical formula of the prepared MXene material is V2C.
[0147] Embodiment 14
[0148] This embodiment provides a commercially available accordion-shaped MXene material with a chemical formula of V2C, which is purchased from Beijing Beike New Materials Technology Co., Ltd. The MXene material is subjected to FTIR testing, and the test results show that there is no hydrophilic functional group in the MXene material.
[0149] Comparative Example 1
[0150] The preparation method of the lithium ion aqueous zinc ion battery of Comparative Example 1 is the same as that of Example 1, except that: no MXene material is added in Comparative Example 1.
[0151] The SEM method was used to observe the MXene materials of Examples 1 to 14 respectively. The results showed that the MXene materials finally obtained in Examples 1 to 13 were all single-layered, while the MXene material of Example 14 had a multi-layer accordion-like morphology.
[0152] The MXene materials of Examples 2 to 14 were tested by FTIR spectroscopy, and the results showed that the hydrophilic functional group -OH was distributed in the MXene materials finally prepared in Examples 2 to 13, while the MXene material of Example 14 had no hydrophilic functional group.
[0153] The pretreated zinc sheets were immersed in the electrolytes of Examples 1 to 14 and Comparative Example 1, respectively, and were placed in a refrigerator for 3 days, rinsed with deionized water, and then placed in a vacuum oven for drying. SEM observation was performed, and the results are shown in Tables 1 and Figure 6 shown.
[0154] In order to explore the ion exchange at the interface between the zinc electrode and the electrolyte, the contact angles between the electrolytes of Examples 1 to 14 and Comparative Example 1 and the zinc sheet were tested using a water contact angle meter. The results are shown in Tables 1 and Figure 7 shown.
[0155] In order to study the interfacial Zn of Zn-Zn batteries 2+ The electrochemical impedance test was performed on the symmetrical batteries of Examples 1 to 14 and Comparative Example 1 after 100 cycles. The results are shown in Tables 1 and Figure 8 As shown in the figure, the perturbation voltage is 5mV and the frequency range is 200kHz-100MHz.
[0156] The cycle life of the symmetrical battery at different current densities was studied. Constant current charge and discharge tests were performed on the Zn-Zn batteries of Examples 1 to 14 and Comparative Example 1. The results are shown in Tables 1 and Fig. 9 As shown in the figure, the voltage range is 0.8-1.8V.
[0157] In order to evaluate the stability of the vanadium carbide film during the cycle, SEM observations were performed on the zinc electrodes of Examples 1 to 14 and Comparative Example 1 after the cycles. The results are shown in Tables 1 and Fig.10 shown.
[0158] The charge and discharge capacity of the full batteries of Examples 1 to 14 and Comparative Example 1 was tested using a constant current charge and discharge mode. The battery was charged and discharged 5 times at a low current density (50 mA / g), and then charged and discharged at a high current density (1 A / g). The results are shown in Tables 1 and Fig.11 shown.
[0159] Table 1
[0160]
[0161]
[0162] It can be seen from Table 1 that compared with Comparative Example 1, the dendrite situation on the zinc foil surface of Examples 1 to 14 is significantly improved. Figure 6 a in the figure shows the SEM image of zinc foil after being immersed in 1mol / L zinc sulfate electrolyte for 3 days, b shows the SEM image of zinc foil after being immersed in 1mol / L zinc sulfate + 0.1mol / L vanadium carbide electrolyte for 3 days, and c shows the SEM image of zinc foil after being immersed in 1mol / L zinc sulfate + 0.3mol / L vanadium carbide electrolyte for 3 days. Figure 6 a It can be seen that after the zinc foil was immersed in zinc sulfate electrolyte for 3 days, a large number of blocky dendrites grew on the surface. Figure 6 As can be seen in b, after adding 0.1 mol / L vanadium carbide to the electrolyte, no obvious dendrites were seen on the surface of the zinc foil, but the surface was slightly rough. Figure 6 c It can be seen that after adding 0.3 mol / L vanadium carbide to the electrolyte, a small amount of dendrites appeared on the surface of the zinc foil. It can be seen that when an appropriate amount of vanadium carbide is added to the electrolyte, the dendrite phenomenon on the surface of the zinc foil is significantly suppressed. However, if an excessive amount of vanadium carbide is added to the electrolyte, a small amount of dendrites will appear on the surface of the zinc foil.
[0163] It can be seen from Table 1 that, compared with Comparative Example 1, the contact angles between the electrolytes of Examples 1 to 14 and the zinc sheet are significantly smaller. Figure 7 a in the figure represents the contact angle between the electrolyte of comparative example 1 and the zinc sheet, and b represents the contact angle between the electrolyte of example 1 and the zinc sheet. It can be seen that the contact angle between the zinc sulfate electrolyte of comparative example 1 and the zinc sheet is as high as 101°. In contrast, the contact angle between the electrolyte of example 1 (with vanadium carbide added) and the zinc sheet is significantly smaller, only 72°. This shows that after adding vanadium carbide to the electrolyte, the wettability of the interface between the zinc electrode and the electrolyte is improved, which is beneficial to the uniform deposition of zinc ions and the formation of a smooth SEI film on the surface of the electrode sheet.
[0164] It can be seen from Table 1 that the interface charge transfer resistance of Examples 1 to 14 is significantly lower than that of Comparative Example 1. Figure 8The EIS graphs of the Zn-Zn batteries of Comparative Example 1 and Example 1 after cycling are shown. It can be seen that the interfacial charge transfer resistance of the battery of Example 1 (with the addition of vanadium carbide additive) is significantly lower than that of the battery of Comparative Example 1, indicating that the interfacial charge transfer is improved during the electrochemical reaction. This is mainly due to the Zn 2+ The rapid diffusion at the electrode / electrolyte interface and the vanadium carbide buffer layer accelerate the charge transfer, thus improving the interfacial charge transport performance during the electrochemical reaction.
[0165] It can be seen from Table 1 that, compared with Comparative Example 1, the constant current charge and discharge performance of Examples 1 to 14 is significantly improved. Fig. 9 : are the time-voltage curves of the symmetrical batteries of Example 1 and Comparative Example 1. Fig. 9 a in the figure shows the overview of the long cycle, and b shows the local figure from 0 to 7 hours in figure a. It can be seen that compared with comparative example 1, the Zn-Zn battery of example 1 (adding vanadium carbide) has a higher current density of 0.5 mA / cm 2 , constant capacity is 1mAh / cm 2 It shows good reversibility and has a smaller voltage overpotential, which shows that adding vanadium carbide to the zinc sulfate electrolyte can make the battery have smaller polarization and smaller zinc nucleation energy barrier, and the voltage of the symmetrical battery in comparative example 1 increased significantly after working for about 60 hours, and then the voltage began to fluctuate irregularly. This may be due to the unstable internal environment of the battery, which caused the battery to short-circuit. The electrolyte of Example 1 contains vanadium carbide, and the battery can still work smoothly after 600 hours of circulation. In contrast, the battery with the addition of vanadium carbide additive has a more stable cycle performance, which helps it maintain high capacity and long cycle life.
[0166] It can be seen from Table 1 that compared with Comparative Example 1, the dendrite situation on the zinc negative electrode surface of Examples 1 to 14 after 300 electroplating / stripping cycles is significantly improved. Fig.10 a in the figure shows the SEM image of the zinc negative electrode of the symmetrical battery of comparative example 1 after 300 cycles, and b shows the SEM image of the zinc negative electrode of the symmetrical battery of embodiment 1 after 300 cycles. It can be seen that the zinc negative electrode of comparative example 1 has a high conductivity at 0.5 mA / cm 2 After 300 electroplating / stripping cycles at a current density of 1.5 , the surface of the zinc negative electrode was severely corroded and a large number of dendrites were clearly observed. The size of the dendrites was about 100 microns ( Fig.10 a). However, the surface of the zinc negative electrode of Example 1 did not change significantly after 300 cycles under the same conditions, and there was still no obvious dendrite formation on the negative electrode surface ( Fig.10 b).
[0167] It can be seen from Table 1 that compared with Comparative Example 1, the initial specific capacity and the capacity after 300 electroplating / stripping cycles of Examples 1 to 14 are significantly improved. Fig.11 It can be seen that the initial capacity of the full battery of Example 1 is 237.4 mAh / g, and the capacity decreases to 129.9 mAh / g after 300 cycles of charge and discharge at a current density of 1 A / g. In contrast, the initial specific capacity of the full battery of Comparative Example 1 is only 174.7 mAh / g, and it drops sharply to 85.3 mAh / g after 300 cycles. It can be seen that adding vanadium carbide to the electrolyte system can not only improve the reaction kinetics of the full battery, but also extend its cycle life.
[0168] It can be seen from Table 1 that compared with Example 14, the contact angle between the electrolyte and the zinc sheet of Examples 1 to 13 is further reduced, and the initial capacity and the capacity after 300 cycles of charge and discharge are further improved. It can be seen that when the MXene material with hydrophilic functional groups distributed on the surface is used as an electrolyte additive, the contact angle between the electrolyte and the zinc sheet can be further reduced, and the initial capacity of the battery and the capacity after 300 cycles of charge and discharge can be further improved.
[0169] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0170] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An electrolyte additive, characterized in that: Including MXene materials.
2. The electrolyte additive according to claim 1, characterized in that: The surface of the MXene material is distributed with hydrophilic functional groups.
3. The electrolyte additive according to claim 2, characterized in that: The hydrophilic functional group includes at least one of an oxygen group, a hydroxyl group, a fluorine group, and a chlorine group.
4. The electrolyte additive according to claim 1, characterized in that: The chemical formula of the MXene material is: m X, wherein M is selected from at least one of V, Ti, Cr, Mo, Nb, Y, Sc, Zr, Hf, Ta, and W, and X is selected from at least one of C and N, and 1≤m≤2.
5. The electrolyte additive according to claim 4, characterized in that: M is selected from V, and X is selected from C.
6. The electrolyte additive according to any one of claims 1 to 5, characterized in that: The MXene material is a single-layer MXene material.
7. A method for preparing the electrolyte additive according to any one of claims 1 to 6, characterized in that: include: (1) mixing a halogen element hydride, a fluoride salt and water to obtain a mixed solution, wherein the electronegativity of the halogen element in the halogen element hydride is lower than that of the fluorine element; (2) Mixing a MXene precursor with the mixed solution and reacting them to obtain a MXene material.
8. The method according to claim 7, characterized in that Also includes: (3) Mixing the MXene material obtained in step (2) with a delamination agent to obtain a single-layer MXene material.
9. The method according to claim 7 or 8, characterized in that: In step (1), the mass ratio of the halogen element hydride to the fluoride salt is 1:(10-15); And / or, the halogen element hydride comprises at least one of HCl, HBr and HI; And / or, the fluoride salt includes at least one of lithium fluoride, sodium fluoride and potassium fluoride.
10. The method according to claim 7 or 8, characterized in that: In step (2), the reaction temperature is 50 to 300° C., and the reaction time is 10 to 50 hours.
11. The method according to claim 8, characterized in that In step (3), the layering agent includes at least one of dimethyl sulfoxide, hexadecyltrimethylammonium bromide and tetramethylammonium hydroxide.
12. An electrolyte, characterized in that: The invention comprises the electrolyte additive according to any one of claims 1 to 6 or the electrolyte additive prepared by the method according to any one of claims 7 to 11.
13. The electrolyte according to claim 12, characterized in that The concentration of the MXene material in the electrolyte is 0.05 mol / L to 0.2 mol / L.
14. The electrolyte according to claim 12 or 13, characterized in that: The electrolyte salt also includes an electrolyte salt, which includes at least one of zinc sulfate and zinc acetate.
15. The electrolyte according to claim 14, characterized in that The concentration of the electrolyte salt in the electrolyte solution is 1 mol / L to 3 mol / L.
16. The electrolyte according to claim 12 or 13, characterized in that: The contact angle between the electrolyte and the zinc sheet is 60° to 97°.
17. An aqueous zinc ion battery, characterized in that: An electrolyte comprising the electrolyte according to any one of claims 12 to 16.
18. An electrical equipment, characterized in that: An aqueous zinc ion battery according to claim 17.
Citation Information
Patent Citations
MXene two-dimensional material and Cu / MXene catalyst, and preparation methods and applications thereof
CN110841721A
Electrolyte for aqueous zinc ion battery and application thereof
CN111900496A
Zinc ion battery electrolyte modifier and preparation method and application thereof
CN112919534A
Electrolyte and preparation method thereof, battery and application of WaC-Mxene
CN117747948A
Additives for suppressing dendritic growth in batteries
US20190044185A1